The effects of SGLT2 inhibitors in patients with metabolic dysfunction-associated fatty liver disease; a narrative review - Mihaela Simona Popoviciu; Lorena Păduraru; Md Mominur Rahman; Fatema Akter Supti; Roxana Adriana Stoica; Delia Reurean-Pintilei; Cristina Ioana Bica; Simona Cavalu (Journal of Mind and Medical Sciences)
Worldwide, metabolic dysfunction-associated fatty liver disease (MAFLD) is a significant public health concern, especially since more than fifty percent of people with type 2 diabetes are affected by it. This pathological condition includes all states of fatty liver disease, from non-alcoholic fatty liver disease (NAFLD) to steatohepatitis (NASH). Prolonged evolutions can lead to cirrhosis and cancer, so treatment must be started early. Hepatic steatosis may be improved by sodium glucose co-transporter 2 inhibitors (SGLT2 inhibitors), which prevent glucose reabsorption in the proximal renal tubule and increase urinary excretion, thus lowering plasma glucose levels. Experimental studies in animal models have suggested that SGLT2 inhibitors may have beneficial modulatory effects on NAFLD and NASH, while numerous clinical trials have demonstrated their favorable effects on the liver enzymes, body mass index, blood lipids, blood glucose, and insulin resistance in NAFLD patients. This review highlights the state of knowledge regarding the epidemiology, diagnosis and pathogenetic pathways of MAFLD, focusing primarily on the effectiveness of SGLT2 inhibitors as a promising drug class in the treatment of NAFLD.